Non-comparative versus Comparative Advertising as a Quality Signal - Winand Emons; Claude Fluet (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Two firms produce a product with a horizontal and a vertical characteristic that we call quality. The difference in the quality levels determines how the firms share the market. Consumers do not observe quality before purchase. Under non-comparative advertising a firm signals its own quality, under comparative advertising a firm signals the quality differential. In both scenarios firms may boast at a cost. In equilibrium firms actually do so, but consumers rationally infer the true quality if firms advertise. Under comparative advertising the firms never advertise together which they may do under non-comparative advertising.
Keywords: D82; L15; M37; 330; advertising; costly state falsification; signalling